2020
DOI: 10.1371/journal.pone.0236286
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of supraclavicular adipose tissue: A human cadaveric study

Abstract: Functional brown adipose tissue (BAT) was identified in adult humans only in 2007 with the use of fluorodeoxyglucose positron emission tomography imaging. Previous studies have demonstrated a negative correlation between obesity and BAT presence in humans. It is proposed that BAT possesses the capacity to increase metabolism and aid weight loss. In rodents it is well established that BAT is stimulated by the sympathetic nervous system with the interscapular BAT being innervated via branches of intercostal nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The neural mechanisms involved in the thermoregulatory control of BAT are well understood in rodents ( Morrison, 2016 ). There is circumstantial evidence that human BAT is under sympathetic control, as human brown adipocytes express adrenoreceptors ( Virtanen et al, 2009 ; Cypess et al, 2015 ; Blondin et al, 2020 ), certain adrenergic agonists have led to BAT thermogenesis ( Kim et al, 2011 ; Cypess et al, 2015 ) and recent evidence of a nerve supply to BAT-like tissue in humans ( Sievers et al, 2020 ). However, there is a lack of understanding of the physiological signals that drive sympathetic nerve activity to BAT in humans.…”
Section: Sympathetic Control Of Batmentioning
confidence: 99%
See 1 more Smart Citation
“…The neural mechanisms involved in the thermoregulatory control of BAT are well understood in rodents ( Morrison, 2016 ). There is circumstantial evidence that human BAT is under sympathetic control, as human brown adipocytes express adrenoreceptors ( Virtanen et al, 2009 ; Cypess et al, 2015 ; Blondin et al, 2020 ), certain adrenergic agonists have led to BAT thermogenesis ( Kim et al, 2011 ; Cypess et al, 2015 ) and recent evidence of a nerve supply to BAT-like tissue in humans ( Sievers et al, 2020 ). However, there is a lack of understanding of the physiological signals that drive sympathetic nerve activity to BAT in humans.…”
Section: Sympathetic Control Of Batmentioning
confidence: 99%
“…Additionally, human rostral medullary raphé neurons are selectively activated in response to a thermoregulatory challenge and point to the location of thermoregulatory neurons similar to those of the raphé pallidus nucleus in rodents ( McAllen et al, 2006 ). A human cadaveric study has also identified a nerve branch to supraclavicular tissue with a similar morphology to BAT, histological analysis of the tissue shows tyrosine hydroxylase immunoreactive structures, which likely represent sympathetic axons ( Sievers et al, 2020 ). These points, taken together, suggest that certain structures that are involved in rodent neural circuitry underlying thermoregulation are also involved in the human circuitry.…”
Section: Sympathetic Control Of Batmentioning
confidence: 99%
“…White adipose tissue is the major site of lipid storage whereas brown adipose tissue is involved in whole body thermogenic regulation as it contains mitochondrial uncoupling protein 1 (UCP1). In rodents, brown adipose tissue is sympathetically innervated [ 299 , 300 , 301 , 302 ], while it is only recently that a nerve has been associated with brown-like adipose tissue deposits in humans [ 303 ]. High fat diet induced obesity is reduced by inhibiting Thp1 or in Thp1 deficient mice and this correlates with activation of uncoupling protein 1 (UCP1) mediated thermogenesis [ 282 ].…”
Section: 5-ht 3 Receptors In Whole Body Metabolismmentioning
confidence: 99%
“…Accrual of new thermogenic adipose tissue can be stimulated by chronic cold exposure, extensive skin burns, and catecholamine producing tumors [7][8][9], all of which can acutely activate existing thermogenic adipocytes [10,11]. Formation of new thermogenic adipose tissue must involve the generation of new adipocytes expressing the characteristic mitochondrial uncoupling protein 1 (UCP1), and the dense vasculature and innervation that distinguishes thermogenic from white adipose tissue [12][13][14][15]. Increased vascular density is required to facilitate oxygen consumption and heat dissipation, and increased innervation sustains thermogenesis through sympathetic signaling [13].…”
Section: Introductionmentioning
confidence: 99%
“…In adults, thermogenic adipose tissue develops in response to chronic cold exposure, extensive skin burns, and catecholamine producing tumors [8][9][10][11][12]. Formation of new thermogenic adipose tissue involves the generation of new adipocytes expressing the characteristic mitochondrial uncoupling protein 1 (UCP1) of new vasculature to facilitate oxygen consumption and heat dissipation [13][14][15][16], and of new innervation to mediate sympathetic signaling [13]. Signaling between multiple cell types is likely to be involved in the process of tissue expansion; for example, adipocytes secrete factors that induce vascularization and innervation [17], catecholamines can stimulate angiogenesis, and progenitor cells niched in the newly forming vasculature can differentiate into thermogenic adipocytes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%